RANKL expression in rat periodontal ligament subjected to a continuous orthodontic force. - Kim, T; Handa, A; Iida, J; Yoshida, S (2007)
OBJECTIVES: This study investigated longitudinal changes in receptor activator NF kappa B ligand (RANKL) expression in periodontal ligament (PDL) cells subjected to a continuous orthodontic force. DESIGN: Fifty-five-day-old male Wistar rats were divided into experimental and control groups. The experimental group had the first molars laterally expanded by a continuous orthodontic force. In each group, the horizontal section specimens were embedded in OTC compound and frozen at 0, 1, 3 and 7 days after the expansion. Sections were observed by immunostaining with anti-RANKL and the tartrate-resistant acid phosphatase (TRAP) staining. RESULT: Immunoreaction of RANKL and TRAP-positive cells were observed in the distal region of the controls and on the compressed side of the expansion group in the 3 and 7 days. Immunoreaction of RANKL was also observed after 1 day on the compression side of the expansion group, but here TRAP-positive cells were few. CONCLUSIONS: The experiments have showed that PDL cells are continuously producing RANKL on the PDL pressure side of rats subjected to mechanical stress with a continuous orthodontic force, there was no noticeable the excessive appearance of osteoclasts however. Considering this, it is expected that not only RANKL production but also other cytokines play an important role in the balancing adjustment in the alveolar bone remodeling.